An Analysis of The Acceptance of Mobile-based Assessment for Student’s Creative and Critical Thinking - Ridhoni, Wahyu; Setyosari, Punaji; Ulfa, Saida; Kuswandi, Dedi (CV. Edutechnium Indonesia, 2024)
Creative and critical thinking are two very important abilities to 21st Century. Previous mobile-based assessments have been carried out, but nothing has been used to measure creative and critical thinking. The Technology Acceptance Model (TAM) is used to see the acceptability of mobile-based assessments for creative and critical thinking. In this research, TAM is used at the prototype stage, where it is important to see the initial response of prospective users. One external variable is added to the main TAM version, namely Skill to use a smartphone. The sample of this research was 71 Informatics Engineering students. The results obtained are: (1) Mobile-based assessment for creative and critical thinking can be accepted by prospective users, (2) Skill to use a smartphone can be ignored, considering that this variable is not significant for acceptance. In other words, even though their skills are low or high, participants will still accept technology, (3) Perceived Ease to Use must be of concern because this variable is the one that has the greatest influence in the acceptance model. How to design applications that are clear, easy to understand, and have a good interaction experience will drive user acceptance.